Integrative Medicine and Mood, Emotions and Mental Health - Shah, Anuj K; Becicka, Roman; Talen, Mary R; Edberg, Deborah; Namboodiri, Sreela (Primary care, 2017)
An integrative approach to individuals with mood, emotional or mental health concerns involves a comprehensive model of care that is person-centered. Integrative medicine builds on a patient's personal meaning and goals (spiritual aspects) and includes herbal therapies, nutritional support, movement and physical manipulative therapies, mindfulness, relaxation strategies, and psychotherapies.